The architecture of cell differentiation in choanoflagellates and sponge choanocytes - Laundon, Davis; Larson, Ben T.; McDonald, Kent; King, Nicole; Burkhardt, Pawel (PLOS Biology, 2019)
3D electron microscopy of choanoflagellates and sponge choanocytes reveals a remarkable variety of cell architecture and suggests that cell type differentiation may have been present in the stem lineage leading to the animals.